2020
DOI: 10.24275/rmiq/ia1420
|View full text |Cite
|
Sign up to set email alerts
|

Acidogenesis/methanogenesis from acid cheese whey in hybrid-UASB reactors

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Slaughterhouse wastewater (SWW) is a residue characterized by a high load of animal derivatives, such as blood and inedible tissues, and pathogenic organisms, making it a potential risk to animal and human health (Franke-Whittle and Insam, 2013;Cárdenas-Medina et al, 2020). Additionally, the large volumes of SWW produced become its management a challenge, as its improper and unsafe disposal can cause serious environmental issues (Arvanitoyannis and Ladas, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slaughterhouse wastewater (SWW) is a residue characterized by a high load of animal derivatives, such as blood and inedible tissues, and pathogenic organisms, making it a potential risk to animal and human health (Franke-Whittle and Insam, 2013;Cárdenas-Medina et al, 2020). Additionally, the large volumes of SWW produced become its management a challenge, as its improper and unsafe disposal can cause serious environmental issues (Arvanitoyannis and Ladas, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…SWW treatment involves several processes, including anaerobic digestion (AD), composting, alkaline hydrolysis, and incineration (Harris and McCabe, 2015). Among these treatments, AD stands out as it has the additional advantages of nutrient recycling and methane production (Franke-Whittle and Insam, 2013;Cárdenas-Medina et al, 2020). Indeed, SWW is considered a suitable substrate for AD due to its high methane yield potential (Palatsi et al, 2011); however, the high protein concentration usually found in SWW can lead to AD inhibition as a consequence of ammonium (NH + 4 ) and longchain fatty acid (LCFA) accumulation, which are byproducts of protein and fat hydrolysis (Hernández-Fydrych et al, 2018).…”
Section: Introductionmentioning
confidence: 99%